Diaphragm Breathing Exercise untuk Mengatasi Kecemasan pada Ibu Hamil - Dahliah Eliya; Nada Septa; Ummu Syafa Adila; Rana Amelia; Rosyati Pastuty (Politeknik Piksi Ganesha Indonesia, 2023)
Most pregnant women often experience pregnancy complaints such as fatigue, shortness of breath when entering the third trimester, and anxiety when facing labor. The aim is to provide the community with reduced anxiety in pregnant women by doing diaphragmatic breathing exercises. The method used is playing videos and doing diaphragmatic breathing exercises. The target of this community service activity is to improve lung function, relieve fatigue, and relieve pain in pregnant women to reduce anxiety during pregnancy